Functional echolalia in autism speech: Verbal formulae and repeated prior utterances as communicative and cognitive strategies - Xie, Fan; Pascual, Esther; Oakley, Todd (Frontiers in Psychology, 2023)
Echolalia, the echoing of prior speech, is a typical characteristic of autism. Long considered meaningless repetition to be avoided, echolalia may in fact be used functionally in autism. This paper explores the functions of echolalia by children with autism. Based on two prior studies, we designed an elicitation task involving images of 12 professions (teacher) and 12 objects (birthday cake) commonly associated with given conventionalized expressions in Mandarin (e.g., “sheng ri kuai le!” ‘Happy birthday!’). Eight Chinese children with autism (mean age: 55.50 ± 8.64) were asked to name and describe these images. All our participants produced a relatively high proportion of echolalia, mostly for naming, description, and topic development, a small percentage being used as conversation maintenance strategy or as cognitive strategy. This indicates that echolalia is often used communicatively in autism speech.